Understanding environmental policy convergence: the power of words, rules and money - Jörgens, Helge (Cambridge Univ. Press, 2014)
"Over recent decades national environmental policies have become increasingly alike. This book analyses the driving forces of this process of policy convergence, providing an in-depth empirical analysis of the international forces at work. It does so by investigating how four countries - France, Hungary, Mexico and the Netherlands - have shaped their domestic environmental policies in the context of international institutions and relationships, while taking into account various domestic factors and national conditions. Employing a qualitative approach, the authors seek to deepen understanding of the processes and mechanisms through which international forces such as legal harmonisation, institutionalised information flows and global trade dynamics affect domestic environmental policy change. Together with its companion volume Environmental Policy Convergence in Europe: The Impact of Trade and International Institutions (2008) this book provides a 'showcase' of mixed methodologies, combining quantitative and qualitative approaches in an innovative way"--